2017
DOI: 10.1016/j.abrep.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Ordinary people associate addiction with loss of free will

Abstract: IntroductionIt is widely believed that addiction entails a loss of free will, even though this point is controversial among scholars. There is arguably a downside to this belief, in that addicts who believe they lack the free will to quit an addiction might therefore fail to quit an addiction.MethodsA correlational study tested the relationship between belief in free will and addiction. Follow-up studies tested steps of a potential mechanism: 1) people think drugs undermine free will 2) people believe addictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 103 publications
(43 citation statements)
references
References 45 publications
3
37
0
3
Order By: Relevance
“…Implications and Directions for Future Research The findings reported in this paper have theoretical implications for both the psychology of free will belief and political psychology. First, these findings provide further and more direct support for previous work conducted on free will belief as motivated social cognition (Clark, Baumeister, et al, 2017;Clark et al, 2014;Clark, Shniderman, et al, 2018;Clark, Winegard, & Baumeister, 2019;Vonasch et al, 2017). The work reported here demonstrates that belief in free will is linked to a desire to hold people accountable for their moral wrongdoing, and that free will attributions vary as a function of the valence of the action, how moral or immoral it is perceived to be, and even who the target is.…”
Section: Overview Of Findingssupporting
confidence: 81%
“…Implications and Directions for Future Research The findings reported in this paper have theoretical implications for both the psychology of free will belief and political psychology. First, these findings provide further and more direct support for previous work conducted on free will belief as motivated social cognition (Clark, Baumeister, et al, 2017;Clark et al, 2014;Clark, Shniderman, et al, 2018;Clark, Winegard, & Baumeister, 2019;Vonasch et al, 2017). The work reported here demonstrates that belief in free will is linked to a desire to hold people accountable for their moral wrongdoing, and that free will attributions vary as a function of the valence of the action, how moral or immoral it is perceived to be, and even who the target is.…”
Section: Overview Of Findingssupporting
confidence: 81%
“…Another analysis suggests that there may be individual differences such that people who are particularly inclined to see a variety of negative actions and outcomes (e.g., homelessness, drug addiction) as having moral significance are also more inclined to believe that people have freedom and control over those actions and outcomes (Everett et al, 2017). Relatedly, people tend to downplay their own free will when considering the morally negative consequences of their own behavior (Vonasch, Clark, Lau, Vohs, & Baumeister, 2017). Such results seem to suggest that free will is largely about moral responsibility.…”
Section: The Function Of Free Will Beliefsmentioning
confidence: 99%
“…Note, however, that latter view (overwhelming cravings) is not only used by opponents but by some who embrace its conclusion. Indeed, experimental studies and surveys by Vonasch, Clark, Lau, Vohs, and Baumeister (2017--this issue) have confirmed that many people in the general public associate addiction with loss of free will, in the form of being unable to resist addictive cravings.…”
Section: Theory: Free Will and Addictionmentioning
confidence: 99%